Implementation of a CNC E-Module Integrating Pancasila Values at Angkasa Aviation Vocational High School, Malang - Fadillah, Faqih; Zakka Agustin, Rizkika; Rizky Septiawan, Diama; Dwi Putra, Agus (Faculty of Engineering University of Pahlawan Tuanku Tambusai, 2025)
The high unemployment rate among Vocational High School (SMK) graduates indicates a gap between graduates’ competencies and labor market demands, particularly in machining engineering. Vocational education also tends to emphasize technical skills without sufficient reinforcement of character and moral values. This community service activity aims to implement a Computer Numerical Control (CNC) e-module integrated with Pancasila values to enhance technical competencies while fostering students’ character development. The methods include needs analysis, e-module design, learning implementation, and evaluation. The analysis of pretest and posttest results shows a significant improvement, demonstrating the effectiveness of the e-module in improving CNC competencies and internalizing Pancasila values.